2016
DOI: 10.1016/j.rppede.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiorespiratory fitness and body fat in girls

Abstract: Objective:To estimate the prevalence of low cardiorespiratory fitness and its association with excess body fat, considering the sexual maturation and economic level in female adolescents.Methods:Cross-sectional, epidemiological study of 1223 adolescents (10-17 years) from the public school system of Cascavel, PR, Brazil, in 2006. We analyzed the self-assessed sexual maturation level (prepubertal, pubertal and post-pubertal), the economic level (high and low) through a questionnaire and body fat (normal and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The correlations between the independent variables and HRPF measures using r coefficient were summarized in Table 3. Weight and BMI showed high significant positive correlation with BF % (r = 0.75, p = 0.000 and r = 0.80, p = 0.000, respectively) and little positive correlation with SRT (r = 0.17, p = 0.01 Open Journal of Therapy and Rehabilitation At the population level, body composition can be used to assess the nutrition status and to study both the determinants and consequences of malnutrition and/or other risk factors [35]. Body composition is expressed as BF % when used as one of HRPF components and it is considered to be a good indicator [36].…”
Section: Resultsmentioning
confidence: 99%
“…The correlations between the independent variables and HRPF measures using r coefficient were summarized in Table 3. Weight and BMI showed high significant positive correlation with BF % (r = 0.75, p = 0.000 and r = 0.80, p = 0.000, respectively) and little positive correlation with SRT (r = 0.17, p = 0.01 Open Journal of Therapy and Rehabilitation At the population level, body composition can be used to assess the nutrition status and to study both the determinants and consequences of malnutrition and/or other risk factors [35]. Body composition is expressed as BF % when used as one of HRPF components and it is considered to be a good indicator [36].…”
Section: Resultsmentioning
confidence: 99%
“…In a similar cross-sectional epidemiological study of 1223 Brazilian adolescents, Minatto et al [ 34 ] found a proportion of non-fit girls of 51.3%, which was positively influenced by low economic status. Furthermore, a recent investigation revealed that poor aerobic fitness was associated with reduced adolescent neuroplasticity, cognitive function, and academic performance [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased body adiposity had been inversely related to cardiorespiratory fitness amongst girls in a study with 1,223 adolescents in the city of Cascavel (PR), South Brazil [13].…”
Section: Discussionmentioning
confidence: 99%